Relationship Between Extraversion and Gambling Tendencies Among Students in Nyamira South-Sub County, Kenya - Nyamogo, Andrew omari; Owaa, Judith; Mwebi, Bernad (International Journal of Novel Research in Education and Learning, 2018)
The Purpose of the study was to explore the relationship between extraversion and gambling tendencies among secondary school students in Nyamira South Sub County, Kenya. Objective was to determine the association between extraversion and gambling tendencies among students in Nyamira South Sub-County. It was informed by Eysenck’s theory of Personality and a conceptual framework. The study adopted concurrent triangulation research design within the Mixed Method Approach. The Units of analysis were 50 secondary schools. The target populations were 12667 students, 50 Guidance and counselling Teachers (G&C Teahers), 52 Deputy Principals and 50 Parents and Guardians. The sample consisted of 370 students (Krejcie and Morgan 1970), 15 G&C teachers, 15 Deputy Principals and 15 Parents and Guardians. The schools were arranged into homogeneous groups and then picked through simple random sampling while the students were selected through simple random sampling. Data was collected through use of questionnaires and interview schedule. To ensure validity of instruments, the instruments were developed under close guidance of the researchers’ Supervisors. To test for reliability, test-retest technique was applied and a correlation coefficient of 0.797 was obtained. Data was analysed using descriptive statistics such as percentages, mean and frequency counts and inferential statistics such as Karl Pearson’s and correlation and regression analysis. Qualitative data was analyzed on the basis of themes and sub-themes that emerged from the study. The study found out that there was a statistical significant association between extraversion and gambling tendencies ( , = 12.558 ˃ = 3.84). The study concludes that Students exhibiting strong extroversive personality subtype traits have a higher frequency of gambling tendencies than other personality subtypes. Furthermore, extroverts are more likely to develop into pathological gamblers as compared to others because more are easily addicted. This study may be significant to Students in secondary schools, G&C teachers, Parents and Guardians and Board of Management of schools. A study on effects of gambling in teaching and learning in secondary schools in Kenya would expound the present study.
Keywords: Gambling tendencies; Secondary school students; Instruments; Conceptual framework